Predicting Dendroctonus pseudotsugae (Coleoptera: Curculionidae) Antiaggregation Pheromone Concentrations Using an Instantaneous Puff Dispersion Model. Issue 2 (5th September 2014) - Strand, Tara M.; Ross, Darrell W.; Thistle, Harold W.; Ragenovich, Iral R.; Guerra, Ivonne Matos; Lamb, Brian K.
Abstract : An instantaneous puff dispersion model was used to assess concentration fields of the Douglas-fir beetle, Dendroctonus pseudotsugae Hopkins, antiaggregation pheromone, 3-methylcyclohex-2-en-1-one (MCH), within a 1-ha circular plot. Several combinations of MCH release rate and releaser spacing were modeled to theoretically analyze optimal deployment strategies. The combinations of MCH release rate and releaser spacing used in the modeling exercise were based on results of previous field studies of treatment efficacy. Analyses of model results suggest that a release rate up to six times the initial standard, at a correspondingly wider spacing to keep the total amount of pheromone dispersed per unit area constant, may be effective at preventing Douglas-fir beetle infestation. The model outputs also provide a visual representation of pheromone dispersion patterns that can occur after deployment of release devices in the field. These results will help researchers and practitioners design more effective deployment strategies.